2015
DOI: 10.5089/9781484328439.001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Productivity Growth in Middle Income Countries

Abstract: Many small middle-income countries (SMICs) in sub-Saharan Africa (SSA) have experienced a moderation in growth in recent years. Although factor accumulation, most notably capital deepening, was crucial to the success of many SMICs historically, this growth model appears to have run its course. The analysis in this paper suggests that the decline in the contribution of total factor productivity (TFP) to growth is largely responsible for the slowdown in trend growth in many SMICs, which highlights the need for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…That is, the nominal GDP, encompassing price changes, and thereby affecting the behavior of consumers and entrepreneurs, as well as other economic entities and phenomena, describes the changes in economic reality. But on the other hand, the relationship between inflation and productivity growth is found to be negative in cross-country empirical studies (Abdychev et al, 2015), and incomes of the population are negatively affected by inflation as well (Leonidova, 2019), which leads to a violation of qualitative characteristics of growth in the processes of its formation and manifestation. Another study suggests that before reaching some threshold level, inflation has a positive impact on growth (Malik et al, 2021).…”
Section: Egqi and Gdp Per Capita Comparisonmentioning
confidence: 97%
“…That is, the nominal GDP, encompassing price changes, and thereby affecting the behavior of consumers and entrepreneurs, as well as other economic entities and phenomena, describes the changes in economic reality. But on the other hand, the relationship between inflation and productivity growth is found to be negative in cross-country empirical studies (Abdychev et al, 2015), and incomes of the population are negatively affected by inflation as well (Leonidova, 2019), which leads to a violation of qualitative characteristics of growth in the processes of its formation and manifestation. Another study suggests that before reaching some threshold level, inflation has a positive impact on growth (Malik et al, 2021).…”
Section: Egqi and Gdp Per Capita Comparisonmentioning
confidence: 97%
“…Thus, they concluded that the rise in the labour participation rate would initiate competitiveness and economic growth. Alternatively, Abdychev et al (2014) pointed out a negative influence of labour participation rates, especially among female workers. However, the relationship turned positive after adjusting the share of the agriculture sector to the GDP, and this illustrated that most women were involved in low-end productivity in the agriculture sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in the late 1980s, transition has referred to the transformation efforts made by former Soviet Union members to move from centrally planned to market economies. More recently, green transition referred to "fostering economic growth and development, while ensuring that natural assets continue to provide the resources and environmental services on which our well-being relies" (see OECD Green Growth and Sustainable Development 4 ).…”
Section: The Context: What Is Transition?mentioning
confidence: 99%